Validation Study of Simplified Soil Mechanics Method Design with Kentledge Pile Loading Test of Bored Pile - Lilies Widojoko (International Conference on Engineering and Technology Development (ICETD), 2012)
The use of static load testing in optimising design and providing verification of suitability and constructability continues to be unsurpassed in the foundation industry. Another purpose of that load testing is either to validate the design before construction and/or to check compliance with the specification during construction The aim of this paper is to validate the design by comparing the ultimate load of Kentledge bored pile loading test with the its design, using Simplified Soil Mechanics method. The difference between Kentledge loading test and Simplified Soil Mechanics method are 13 % and 25%, if the pile bearing ultimate capacity of Kentledge loading test is computed using Mazurkiewicz and Davisson MT method.